Enhancement of electro-optical and dielectric parameters of a room temperature nematic liquid crystalline material by dispersing multi-walled carbon nanotubes. Issue 3 (19th February 2021) - Singh, Deepa; Singh, U. B.; Dhar, Ravindra; Dabrowski, Roman; Pandey, M. B.
ABSTRACT: We have prepared the composites of a room temperature nematic liquid crystal mixture by dispersing small fractions of Multi-Walled Carbon Nanotubes into its matrix. The electro-optical and dielectric properties of the prepared samples were investigated. The effect of Multi-Walled Carbon Nanotubes on various display parameters of host nematic liquid crystal mixture was observed. The variations in some of the display parameters like dielectric anisotropy, threshold voltage, splay elastic constant and activation energy have been observed for composite systems with respect to pure nematic liquid crystal mixture. Dispersion of Multi-Walled Carbon Nanotubes enhanced the nematic order of liquid crystal host, resulting in the improvement of dielectric and electro-optical parameters of studied composite systems. Graphical abstract: uf0001